Health-related fitness in school children: compliance with physical activity recommendations and its relationship with body mass index and diet quality - José Pino-Ortega; Ernesto De la Cruz-Sánchez; Raúl Martínez-Santos (Archivos Latinoamericanos de Nutrición)
This study establishes the relationship between the compliance with the governmental physical activity guidelines (at least a minimum of one hour of moderate to vigorous physical activity, MVPA, five times a week), health-related physical fitness and different health related lifestyle variables in a representative sample of Spanish children. Subjects were a representative group of scholars from five schools randomly selected in Extremadura, a mainly rural region with a very low population density. Statistical analysis comprises a t-test to calculate physical fitness differences between groups, according to the compliance with the mentioned physical activity guidelines. A multinomial logistic regression coefficient is established to determine the differences between the better physical fitness status group (= percentile 75) and the poorer physical fitness status group (= percentile 25) for each fitness test and gender, body mass index, physical activity, Mediterranean diet index and population size. Main findings show that the compliance with physical activity guidelines result in a better handgrip strength in left hand (p<0.05), leg strength (p<0.000), speed-agility run (p<0.000) and 20 m endurance shuttle run (p<0.000). Being a girl, being overweighed and living in an urban setting are associated with a lower physical fitness (= percentile 25), whereas there is no relationship between diet quality and subjects’ performance in all physical fitness test evaluated. As a conclusion, this study emphasizes the need to promote an active lifestyle in which physical activity suppose a minimum of one hour of regular MVPA, at least five times a week, to achieve a healthy fitness status.